Efectos de productos dopantes en fluidos para pruebas de desplazamiento usando tomografia computarizada (2017)
Colombia is innovating in the use of computerized tomography for the study of enhanced oil recovery methods that could be applied on mature fields, i.e., those that have reached the maximum production and have entered in a declining stage. The computerized tomography has proven advantageous in the medical field and among others. The technique is based in the use of X rays to obtain digitally reconstructed cross sections from fluids, objects or materials. The fluids visualization can be improved using contrast products, also known as dopants. In the petroleum industry, those products are used in displacement tests with the purpose of generating a remarkable contrast for the injected fluids in the rock. Its use has been poorly documented, whereby, the present research has the objective of developing an initial study on the effect that dopants will have in images visualization and fluids viscosity. For this purpose, a bibliographical review about the effect on images resulting from these processes was carried out. Moreover, an experimental design was elaborated to evaluate the effect of those products on viscosity for two petroleum and a brine sample. The above, aiming to establish conceptual and experimental bases that contribute to the learning curve about the use of this technique in the petroleum engineering.